Crystallization behavior and morphology of polylactide and PLA/clay nanocomposites in the presence of chain extenders. Issue 5 (15th October 2012) - Najafi, N.; Heuzey, M.C.; Carreau, P.J.
Abstract The effect of clay and chain extender on the nonisothermal, isothermal crystallization kinetics, and morphology of polylactide (PLA) was investigated in this study. PLA and PLA‐based nanocomposites containing 2 wt% organoclay were prepared via melt compounding. Three commercially available chain extenders were used: polycarbodiimide (PCDI), tris(nonylphenyl) phosphite (TNPP), and Joncryl ADR4368F. The nanoclay particles were found to act as nucleating agents. Chain extender incorporation, however, had diverse effects on both crystallization rate and degree of crystallinity. Nonisothermal DSC results revealed that the addition of PCDI increased the cold‐crystallization temperature (Tc) from 106 to 114°C, reduced the degree of crystallinity from 6.3 to 5.3%, and resulted in the formation of bimodal melting peaks in PLA. On the other hand, the reduction of chain ends in the presence of TNPP resulted in a significant increase of the crystallization rate and degree of crystallinity from 6.3 to 15.2%. In the case of Joncryl, its incorporation led to the formation of a long‐chain branching structure, which disrupted the chain packing. Therefore, the degree of crystallinity (from 6.3 to 1.6%) and the rate of crystallization decreased, while Tc was increased from 106 to 122°C in the presence of Joncryl. POLYM. ENG. SCI., 2013. © Society of Plastics Engineers